Avaliação funcional indireta e descritiva: uma caracterização metodológica de trabalhos empíricos - Pickart, Tataína Iara Moreno (2019)
The term functional analysis is used by behavior analysts to refer to the demonstration of dependence relations between environmental and behavioral variables. The term functional assessment is used in the same manner and also describes pre-intervention procedures that aim to identify environmental variables that control a target behavior. This assessment process may be: (a) indirect, in which interviews, questionnaires or scales are used to search the function; (b) descriptive, in which the target behavior is directly observed, and the relationships between it and the environmental events that precede and follow the behavior are described; and (c) experimental, which involves meticulous manipulation of environmental variables of which a behavior might be a function of. Considering that there is no literature review which includes only indirect and/or descriptive functional evaluations, this study aimed to characterize empirical studies in behavior analysis which have implemented functional assessments with indirect and/or descriptive procedures. Five distinct databases were used, and only empirical studies published between 2014-2018 were included. A total of 38 articles met the inclusion criteria. The obtained results showed great qualitative diversity in indirect and descriptive assessment procedures, and most of data corresponded to those reported in literature reviews on experimental procedures. In general, it is possible to conclude that the analyzed studies lack technological descriptions of their procedures, which hindered the identification and description of methodological patterns in conducting the assessments. That may hinder future replication of these studies